Synthesis, Characterization and Antibacterial Activity Evaluation of New Indole-Based Derivatives - Sulaiman, Ahmed T.; W. Sarsam, Susan (Iraqi Journal of Pharmaceutical Sciences, 2020)
A new series of N-acyl hydrazones (4a-g) derived from indole-3-propionic acid (IPA) were synthesized. These N-acyl hydrazones were prepared by the reaction of 3-(1H-indol-3-yl) propane hydrazide and aldehyde in the existence of glacial acetic acid as a catalyst. 1HNMR and FT-IR analyses were used to identify the synthesized compounds and they were in vitro evaluated as antibacterial agents against six different types of microorganisms by using well diffusion method. All the tested N-acyl hydrazones (4a-g) displayed moderate activity against the Gram-negative E.coli, comparable to that of Amoxicillin. Some of the tested N-acyl hydrazones also exhibited intermediate activity against some of the examined Gram-positive and Gram-negative bacteria. While no activity was exhibited by any of the examined compounds against the Gram-positive S. aureus.